Analisa Usaha Tani Jagung Manis (Bonanza F1) di Kebun Percobaan Lempake, Kota Samarinda - Abdillah, Al Hibnu; Saputra, Junaidi Pangeran (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Sweet corn is a food commodity that community are interested in. The increase in population has an impact on high demand for food. An Experimental Garden Lempake which is under the auspices of the Agriculture Instrument Standardization Agency (BSIP) East Kalimantan, has a function as a research/study location, nursery, genetic resource collection garden, field work practice (PKL) and community service program (KKN) location for students, agro-tourism, technical guidance in agricultural innovation, participates in cultivating sweet corn Bonanza F1. The income value and R/C ratio of corn farming still unknown. The study aimed was to determine the income value and R/C ratio of sweet corn farming in Experimental Garden Lempake. The study was conducted in Experimental Garden Lempake, Samarinda City. Started on May up to August 2023. The sampling uses purposive sampling method, which is conducted by studies deliberately in consideration of the number, ability or information of the respondents. The data analysis method used is descriptive quantitative using the income analysis formula. Corn farming was conducted in Experimental Garden Lempake by 600 m2 a land area it was able to provide an income of IDR 885,000, by three types of products namely corn cobs, baby corn and corn waste. The revenue obtained was IDR 3,786,000 by the costs incurred amounting to IDR 2,902,000. Revenue will be even greater if implementing agricultural intensification and extensification. Opening new land will increase the number of stalks even more, thereby increasing revenues from cobs, baby corn and corn waste.